An Important Part Of Voice And Tone Of Speech In Integrated Skills - Mamatkulova Fotima Ashirkulovna; Morozova Valentina Yurievna; Jumaniyozova Parizod Shonazar qizi; Akramova Malika Valijonovna (Genius Journals, 2025)
The learning situation is influenced by various aspects of the learning environment, such as classroom discourse, tone of voice, and content. These factors influence student interaction, understanding, and motivation. Constructive criticism helps improve learning, while peer tutoring supports collaboration and knowledge sharing. This article examines how these elements shape the classroom experience and contribute to effective learning
Keywords: Learning situation; academic discourse